Templated microbiology comments with candiduria to enhance antimicrobial stewardship - Weston R. Schartz; Nicholas Bennett; Laura Aragon; Kevin Kennedy; Austin Wilson; Sarah Boyd; Matthew Humphrey; Cynthia Essmyer (Cambridge University Press, 2022)
Abstract Objective: To evaluate the effect of templated microbiology reporting comments on antifungal utilization in patients with candiduria. Design: In this retrospective, quasi-experimental study, we evaluated a preimplementation cohort (June 2018-January 2019) compared with a postimplementation cohort (June 2019-January 2020). Setting: A multisite health system including 1 academic hospital and 4 community hospitals. Patients: Patients were aged ≥18 years, were hospitalized, and had candiduria documented at least once during their admission. The study included 156 patients in the preimplementation period and 141 patients in the postimplementation period. Methods: In June 2019, Saint Luke's Health System implemented the use of templated comments for urine cultures with Candida spp growth. When Candida is isolated, the following comment appears in the microbiology result section: "In the absence of symptoms, Candida is generally considered normal flora. No therapy indicated unless high risk (pregnant, neonate, or neutropenic) or undergoing urologic procedure. If Foley catheter present, remove or replace when able." The primary outcome was rate of antifungal prescribing. Results: Antifungal administration within 72 hours of a culture identifying a Candida spp occurred in 75 patients in the preimplementation group and 48 patients in the postimplementation group (48.1% vs 34.0%; P = .02). We did not detect a difference between groups in antifungal administration between 73 and 240 hours (1.3% vs 3.5%; P = .26), nor did we detect a difference in median antifungal duration (4 vs 3 days; P = .43). Conclusion: Using a templated comment with urine cultures reduced antifungal prescription rates in hospitalized patients with candiduria. This strategy is a low-resource technique to improve antimicrobial stewardship.